Characterization of carotenoids in Lycium barbarum fruit by using UPC2-PDA-Q-TOF-MSE couple with deep eutectic solvents extraction and evaluation of their 5α-reductase inhibitory activity - Yu, Zhonglian; Xia, Mengqin; Li, Xueping; Wang, Rui; Liu, Wenjing; Zheng, Ruirong; Wang, Zhengtao; Yang, Li; Shi, Yanhong (Frontiers in Chemistry, 2022)
Carotenoids from Lycium barbarum fruits have possessed pharmacological efficacy against eye diseases, cardiovascular disorders, cancer, and benign prostatic hyperplasia. However, the efficient extraction, rapid characterization and activities evaluation of Lycium carotenoids remains a challenge. To concentrate and characterize Lycium carotenoids, we have developed ultrasound-assisted extraction methods with different deep eutectic solvents (DESs) and analyzed carotenoids by ultra-performance convergence chromatography coupled with photo diode array detector and quadrupole time-of-flight mass spectrometry (UPC2-PDA-Q-TOF-MSE). DESs containing choline chloride and malonic acid presented better extraction efficiency and were more environmentally friendly than other extraction methods. Carotenoids were more quickly profiled (in 11 min) by UPC2 compared to by UPLC (in 35 min), with seventeen main peaks were characterized in the MS fragmentation patterns. The in vitro 5α-reductase inhibitory activity of DESs extracts, fractions and components were subsequently assessed, and the predominant component zeaxanthin dipalmitate (ZD) exhibited potent inhibitory activity. Our study provides a chemical and pharmacological basis for the further development of potential new drugs based on Lycium carotenoids.